Elliptical equation:

$(x+1)^2 + (\frac y 3)^2 = 1$

I need to find the unit tangent vector for it, so I need the derivative, but I have no idea how to differentiate this equation.

  • $\begingroup$ Parametrize your curve as $(\cos(t) - 1, 3\sin (t))$ with $t \in [0, 2\pi)$ and differentiate. $\endgroup$ – MSDG Sep 10 '18 at 16:35
  • $\begingroup$ Can i derivate $y = 3 * sin t$ ? $\endgroup$ – tre038 Sep 10 '18 at 16:46
  • $\begingroup$ You should differentiate each component to get the tangent vector, i.e. if you parametrize your curve by $\gamma(t) = (x(t), y(t)) = (\cos(t)-1, 3\sin(t))$, then your tangent vector is $\gamma'(t) = \big((\cos(t)-1)', (3\sin(t))'\big).$ $\endgroup$ – MSDG Sep 10 '18 at 16:50

By differentiation on $x$, and getting rid of the denominator


You can take the vector $(y,-9(x+1))$ as the direction of $(dx,dy)$.

After normalization,


| cite | improve this answer | |

We can take the derivative of this equation "implicitly" as the following:

$$9x^2+18x+9+y^2 = 9\to9x^2+18x+y^2=0$$

So, now we implicitly differentiate$$18x\textrm{dx}+18\textrm{dx}+2y\textrm{dy}=0$$We now "divide" by $\textrm{dx}$ (Again, dividing by differentials isn't actually a permitted operation, but as you'll later learn in your mathematical journey, it happens to work nicely in cases like these).$$9(x+1)=-y\frac{dy}{dx}$$Hence,$$-\frac{9(x+1)}y=\frac{dy}{dx}$$

| cite | improve this answer | |


Let $y \not =0$.

Differentiate the equation with respect to $x$:

$2(x+1)+ 2(y/3)(1/3)dy/dx=0$.

$9(x+1) +y dy/dx= 0.$

$dy/dx= -9(x+1)/y$.

Note :

$h(x):= f(g(x)).$

$h'(x)= f'(g(x))g'(x).$

In our equation :

$y=g(x)$, $f(y)=(y/3)^2$.

Hence :

$h'(x)= f'(y)y'= 2(y/3)(1/3)y'$.

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.